(untitled) (International Nexus Multidisciplinary Research Journal, 2025)
Toilet tissue is a widely used hygiene product essential for daily sanitation practices. Despite its intended hygienic purpose, improper handling and poor manufacturing standards may lead to microbial contamination, posing potential health risks to users. This study assessed the microbial safety of different brands of toilet tissues sold in Owerri, Imo State, Nigeria. Six brands labelled A, B, C, D, E and F tissues were analyzed for bacterial and fungal contamination using standard microbiological methods. Samples were serially diluted and cultured on Nutrient Agar, MacConkey Agar, Blood Agar, and Sabouraud Dextrose Agar. Microbial isolates were identified through morphological, biochemical, and microscopic analyses. Results showed varying contamination levels among brands, with the F tissue exhibiting the highest bacterial load (7.1 × 10³ cfu/ml) and fungal count (1.0 × 10² cfu/ml). Enterobacter sp. and Staphylococcus aureus were the predominant bacterial isolates, while Aspergillus spp. and Mucor spp. were the major fungi identified. These findings highlight the need for stricter quality control, improved packaging, and hygienic handling during production and distribution.